2019
DOI: 10.1021/acs.energyfuels.9b01255
|View full text |Cite
|
Sign up to set email alerts
|

Process Modeling and Techno-Economic Analysis of a CO2 Capture Process Using Fixed Bed Reactors with a Microencapsulated Solvent

Abstract: A detailed model of a capsule containing sodium carbonate solution is developed here to study the microencapsulated carbon capture solvents (MECS). A rigorous vapor−liquid equilibrium model is developed for the Na 2 CO 3 −CO 2 −H 2 O system, where liquid-phase nonideality is modeled by the electrolyte nonrandom two-liquid model. The data from the experiments conducted at the Lawrence Livermore National Laboratory is used to obtain a maximum likelihood estimate of the initial solvent concentration inside the ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 32 publications
2
7
0
Order By: Relevance
“…CTP and CL are the tube count calculation constant and the tube layout constant, respectively; for one tube pass, CTP = 0.93 and CL = 0.87 for 30 and 60 equilateral tri pitch. Similar configurations can be found in the modeling studies performed by Kim et al 25 and Kotamreddy et al 26 The heat transfer coefficient between the gas phase and the embedded heat exchanger (h HX ) was calculated using correlations from Penny et al 27…”
Section: Embedded Heat Exchangermentioning
confidence: 89%
See 1 more Smart Citation
“…CTP and CL are the tube count calculation constant and the tube layout constant, respectively; for one tube pass, CTP = 0.93 and CL = 0.87 for 30 and 60 equilateral tri pitch. Similar configurations can be found in the modeling studies performed by Kim et al 25 and Kotamreddy et al 26 The heat transfer coefficient between the gas phase and the embedded heat exchanger (h HX ) was calculated using correlations from Penny et al 27…”
Section: Embedded Heat Exchangermentioning
confidence: 89%
“…Heat exchanger design variables (d t and P t ) are similar to the literature and result in a specific heat exchange area of 53 m 2 /m 3 , which is similar to other studies found in the literature. 26 2.4. Postcombustion CO 2 Capture Process Configuration.…”
Section: { Z Z Z Z Z Zmentioning
confidence: 99%
“…In this study, the breakthrough concentration is assumed to be 10% of the inlet concentration. The breakthrough time is defined as The distribution of the breakthrough times for the PUQ and PUQwD cases are represented by their probability density estimates shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…The feed stream (1) to the carbon capture cycle is assumed to be products of a complete combustion reaction of 1 mol/s of methane, containing 7.52 mol/s N 2 , 2 mol/s H 2 O, and 1 mol/s CO 2 . This flow combination has been addressed in several studies in evaluating a carbon capture cycle 42 or the input stream as a whole is comprised of N 2 , CO 2 , and H 2 O with different mole fractions 6 . Thence, the presence of NO x and other pollutants is ignored in the input stream.…”
Section: System Description and Methodologymentioning
confidence: 99%